Cult of the Dead Cow : how the original hacking supergroup might just save the world - Menn, Joseph (New York : PublicAffairs, 2019)
The shocking untold story of the elite secret society of hackers fighting to protect our privacy, our freedom -- even democracy itself.
"Cult of the Dead Cow is the tale of the oldest, most respected, and most famous American hacking group of all time. Though until now it has remained mostly anonymous, its members invented the concept of hacktivism, released the top tool for testing password security, and created what was for years the best technique for controlling computers from afar, forcing giant companies to work harder to protect customers. They contributed to the development of Tor, the most important privacy tool on the net, and helped build cyberweapons that advanced US security without injuring anyone. With its origins in the earliest days of the Internet, the cDc is full of oddball characters--activists, artists, and musicians--some of whom went on to advise presidents, cabinet members, and CEOs, who now walk the corridors of power in Washington and Silicon Valley. Today, the group and its followers are battling electoral misinformation, making personal data safer, and organizing to keep technology a force for good instead of for surveillance and oppression. Cult of the Dead Cow describes how, at a time when governments, corporations, and criminals hold immense power, a small band of tech iconoclasts is on our side fighting back"--Dust jacket flap.
The players -- An evening in San Francisco -- Texas T-files -- The cons -- Underground Boston -- Back orifice -- One million dollars and a monster truck -- Oxblood -- Much @stake -- Tor and Citizen Lab -- Jake -- Mixter, Muench, and Phineas -- Mudge and Dildog -- The congressman and the trolls -- Epilogue.
Includes bibliographical references (pages 215-233) and index.
HB
Keywords: Cult of the Dead Cow; Hacktivism; Hackers; Computer security; SOCIAL SCIENCE / Sociology / General; Hackers; Computer security; Hacktivism